Efeitos da lei de responsabilidade fiscal sobre as despesas públicas dos municípios do estado do Piauí - Carvalho, Paulino Fortes (2007)
The end of the nineties was marked by a deep transformation in the economical and political scenery of Brazil, with the implementação of conducts that looked for the adaptation of our country to the new demands of the international scenery. So that the country incorporated the notions of competitiveness and development, it was necessary that the public section of that also your share in this search, and that the public administrators' financial activities if they adapted to the new model of State, with the most rational control and probo of the Budget Público.Neste context, he went into effect in 04.05.2000, the Law Complemental no. 101 - the call Law of Fiscal Responsibility (LRF). it Appears with the intention of limiting the endividamento of the Union, of States and Municipal districts, while it defines the basic beginnings of responsibility, derived of the prudence notion in the administration of public resources. The Problem of this work is: which the effect of LRF and of the constitutional limits of expense with education and health on the public expenses of the municipal districts of Piauí? The general Objective is to analyze the effect of LRF and of the constitutional limits of the education and health on the public expenses of the municipal districts of the State. Specifically, to verify which the municipal districts that are accomplishing LRF, considering the limit of 60% of the Liquid Average Revenue; the municipal districts that are suffering sanctions or vedações for they be between the limit prudencial and the legal limit; the ones that are below the limit prudencial; to analyze the effect of the Law on the municipal districts through the model logit and; to verify the execution of the constitutional limits of the education and health through the model probit. The methodology consisted essentially of the verification of the municipal districts that you/they are accomplishing LRF, through the calculation of the participation of the expenses with personnel in the total of the liquid average revenue of each municipal district and the application of the model logit to verify the effect of the referred Law specifically considering the expense limit with personnel of 54% of the municipal Executive power, considering the variables of control population and GDP. Besides, the model probit was used to verify the effect of the execution of the constitutional limits of the education and health. The results point a positive effect of the Law for most of the municipal districts of Piauí with a fall of 2000 for 2002 of the participation of municipal districts that descumpriram the Law. Besides, the results of the logit appear, in general, a probability of the municipal districts reduce the primary déficts with positive variation, in the average of the municipal districts, in the indexes of the Law, taking the conclusion of the positive effect of the mentioned Law in the contention of the public expenses in the municipal districts of Piauí. The results of the probit show a positive effect, for the municipal districts of Piauí, in the execution of the constitutional limits of the education and health, because I increase in the index of the expenses with education and with health it increases the probability of amplification of deficits, and as the municipal districts they accomplish the law increasing your expenses with education and health increases the possibility of the execution of the constitutional limits.